PENGEMBANGAN PERMAINAN LUDO KING OF ACCOUNTING (DOTING) SEBAGAI MEDIA PENGAYAAN PADA MATERI JURNAL KHUSUS PERUSAHAAN DAGANG - Titik Fauziati; Joni Susilowibowo (FKIP Unswagati, 2021)
AbstractThis research was conducted with the aim of analyzing the development process and analyzing the feasibility of the ludo king of accounting game which was developed as an enrichment media in special journal material for trading company class XI Accounting in SMK Negeri 1 Sooko Mojokerto. The development model in this study is the ADDIE model which includes the Analyze, Design, Development, Implementation, and Evaluation stages. However, the implementation and evaluation stages in the ADDIE development model were not carried out due to certain conditions and time constraints. The test subjects in the research are material experts and media experts. The instrument used for data collection in the form of a study sheet in the form of an open questionnaire and a sheet of validasi in the form of a closed questionnaire. The method used to analyze data from study sheets and validation of material and media was carried out in a quantitative descriptive manner based on a Likert scale. The results obtained in the form of the feasibility of the material which shows the average percentage of material validation results of 87,71% with a very decent category and the percentage of results of the media validation of 88% with a very decent category. Thus, the game of ludo king of accounting is declared to be very suitable to be used as enrichment media in special journal material for trading companies of class XI Accounting.Keywords: Enrichment Media, Ludo King of Accounting Game, ADDIE Development Model.